2018
DOI: 10.1007/s00436-018-5764-3
|View full text |Cite|
|
Sign up to set email alerts
|

Green drugs in the fight against Anisakis simplex—larvicidal activity and acetylcholinesterase inhibition of Origanum compactum essential oil

Abstract: Anisakiasis is a fish-borne parasitic disease caused by the consumption of raw or undercooked fish, as well as cephalopods, contaminated by third instar larvae (L3) of species belonging to the genus Anisakis (Anisakidae). Origanum compactum is a small herbaceous aromatic plant endemic to Spain and Morocco. In Morocco, the plant is used under infusion to treat heart diseases and intestinal pains or as preservative for foodstuffs. This is the first time that the O. compactum essential oil is tested against the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 49 publications
2
39
1
Order By: Relevance
“…Furthermore, it was shown that thymol may work by blocking octopamine receptors, which are unique to insects and considered as an important target site for pest and vector control [10,14]. On the other hand, the actual role of thymol and carvacrol to interact with the cholinergic system of insects cannot be neglected [62]. Instead, their interaction with the detoxification system of insects can be excluded [63].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that thymol may work by blocking octopamine receptors, which are unique to insects and considered as an important target site for pest and vector control [10,14]. On the other hand, the actual role of thymol and carvacrol to interact with the cholinergic system of insects cannot be neglected [62]. Instead, their interaction with the detoxification system of insects can be excluded [63].…”
Section: Discussionmentioning
confidence: 99%
“…Different activities of Origanum spp. such as antioxidant (Dutra et al, 2019), cytotoxic (Coccimiglio et al, 2016), antimicrobial (Lesjak et al, 2016;Reyes-Jurado et al, 2019), anti-acetylcholinesterase (Abou-Taleb et al, 2016;Hajlaoui et al, 2016;López et al, 2018), antibacterial (da Cunha et al, 2018;Wijesundara & Rupasinghe, 2018), repellent (Govindarajan et al, 2016;La Pergola et al, 2017;Giatropoulos et al, 2018), antifungal (Vinciguerra et al, 2018), allelopathic (Boukaew et al, 2017), phytotoxic (Ibáñez & Blázquez, 2018;Grul'ová et al, 2019) insecticidal (Kim et al, 2016;Szczepanik et al, 2018;Benelli et al, 2019) have been determined in a number of studies.…”
Section: Introductionmentioning
confidence: 99%
“…Plant secondary metabolites represent an ancient and huge source of bioactive molecules of potential interest for developing new insecticides [23,24,25] and antiparasitic drugs [26,27,28,29,30,31]. The genus Origanum L. (Lamiaceae) comprises 43 species (51 taxa) worldwide [32,33,34,35,36,37,38], with its center of diversity in the Mediterranean area [32].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, we hypothesized that the essential oil from this plant species may be exploited further as a useful source of compounds with antiparasitic and insecticide activity. Therefore, boosting our research line focused on disclosing new essential oils and isolated compounds with promising effectiveness against parasites and vectors of public importance [31,58,59,60], herein we evaluated the activity of the essential oil obtained from the Lebanese O. syriacum against the parasitic nematode A. simplex, through larvicidal and penetration assays. Furthermore, this oil was assessed for its bioactivity on the larvae of the mosquito vector C. quinquefasciatus .…”
Section: Introductionmentioning
confidence: 99%